2010
DOI: 10.2147/dmsott.s6935
|View full text |Cite
|
Sign up to set email alerts
|

Past, present, and future: Critical analysis of use of gastric bands in obese patients

Abstract: Adjustable gastric banding (AGB) is quickly becoming the most popular bariatric operation performed in the United States and Canada. Patients are particularly fond of the simplicity of the tool, the relatively low morbidity of the surgery, the quick recovery, and overall results. The gastric band has evolved over its 35-year history into a very successful adjustable tool used to restrict food consumption and limit caloric intake. The percent of excessive weight loss after banding can range from 30%–60% and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 73 publications
0
14
0
2
Order By: Relevance
“…A range of research focused on bariatric patients has shown that people find adherence to the dietary recommendations very difficult in the long term (Hsu et al, 1997 , 1998 ; Elkins et al, 2005 ; Poole et al, 2005 ; van Hout et al, 2005 ; Toussi et al, 2009 ; Snyder et al, 2010 ; Sarwer et al, 2011 ; Chesler, 2012 ; Homer et al, 2016 ). After the initial 6–12 months post-surgery, as the physical limitations ease somewhat with time, adhering to new, drastically smaller portion sizes is believed to be the primary challenge for most of the men and women who undergo the surgery (MacLean et al, 1983 ; Miskowiak et al, 1985 ; Näslund et al, 1988 ; Andersen and Larsen, 1989 ; Lindroos et al, 1996 ; Malone and Alger-Mayer, 2004 ; Sjöström et al, 2004 ; Sarwer et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…A range of research focused on bariatric patients has shown that people find adherence to the dietary recommendations very difficult in the long term (Hsu et al, 1997 , 1998 ; Elkins et al, 2005 ; Poole et al, 2005 ; van Hout et al, 2005 ; Toussi et al, 2009 ; Snyder et al, 2010 ; Sarwer et al, 2011 ; Chesler, 2012 ; Homer et al, 2016 ). After the initial 6–12 months post-surgery, as the physical limitations ease somewhat with time, adhering to new, drastically smaller portion sizes is believed to be the primary challenge for most of the men and women who undergo the surgery (MacLean et al, 1983 ; Miskowiak et al, 1985 ; Näslund et al, 1988 ; Andersen and Larsen, 1989 ; Lindroos et al, 1996 ; Malone and Alger-Mayer, 2004 ; Sjöström et al, 2004 ; Sarwer et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…A sensação de fome induzida por este tipo de prática é constante e o indivíduo sente a sua qualidade de vida reduzida. As complicações associadas a este tipo de cirurgia envolvem a dilatação da bolsa gástrica ou do esófago, a erosão e o deslizo da banda (Snyder et al, 2010). Actualmente, esta técnica é pouco realizada, somente em casos seleccionados, já que a longo prazo não é considerada a melhor opção (Lemos et al, 2005).…”
Section: Cirurgia Bariátricaunclassified
“…Actualmente, esta técnica é pouco realizada, somente em casos seleccionados, já que a longo prazo não é considerada a melhor opção (Lemos et al, 2005). Caso a banda deva ser removida, deve ser tido em consideração a conversão para um outro modelo cirúrgico, como por exemplo para o bypass, devido à grande probabilidade que estes pacientes têm de recuperar o peso perdido (Snyder et al, 2010).…”
Section: Cirurgia Bariátricaunclassified
“…Prevention of recognized early gastric band complications, including acute band obstruction, gastric perforation, bleeding and infection rely on meticulous surgical technique . Occasionally, surgical intervention in the early post‐operative period is required for adjustment or replacement of the device . Proximal pouch enlargements above the band including anterior, posterior and symmetrical dilatation, band erosion and access port or tubing failure are complications that may occur later .…”
Section: Introductionmentioning
confidence: 99%
“…9 Occasionally, surgical intervention in the early post-operative period is required for adjustment or replacement of the device. 10 Proximal pouch enlargements above the band including anterior, posterior and symmetrical dilatation, band erosion and access port or tubing failure are complications that may occur later. 11 The introduction of the pars flaccida approach has significantly reduced the rates of gastric band slippage.…”
Section: Introductionmentioning
confidence: 99%